Actual problems of levying value added tax in modern conditions - Allahverdiyeva, L.M.; Tasmaganbetov, A.B.; Kunurkulzhayeva, G.T.; Baishukurova , Zh.Zh. (BUKETOV BUSINESS REVIEW, 2018)
The role of the value added tax in the implementation of the tax policy of the Republic of Kazakhstan is considered in the article. The authors described the discussion of the replacement of the value-added tax on sales tax. The article contains a list of states that have introduced into their tax systems value-added tax and subsequently refused to use it. The history of changes in the value added tax rates in the Republic of Kazakhstan for 1992-2018 is analyzed. The authors of the article investigated the stimulating and social functions of the value-added tax applied in the international practice of administration. The article considers the current mechanism of calculation and payment of value added tax in the Republic of Kazakhstan. To assess the role of indirect taxes, including the value-added tax in the formation of budget revenues, the receipt of these taxes into the state budget of the Republic of Kazakhstan is analyzed. The authors noted that in the world practice, the most widespread and applicable among indirect taxes are two taxes: value-added tax and sales tax. The article identifies the positive characteristics of the value-added tax in comparison with the sales tax.